MODERNIZATION OF AGRICULTURAL ENTERPRISES AND PROBLEMS OF USING DIGITAL TECHNOLOGIES IN AGRICULTURAL ENTERPRISES OF THE REPUBLIC OF UZBEKISTAN - Professor., G’ulomov Saidasror Sayidaxmedovich (Scholar Express Journals, 2023)
The article discusses the digital transformation of the agro-industrial complex of the Republic of Uzbekistan. An analysis of foreign experience in introducing digital technologies in agriculture was carried out. The main tasks of digital transformation of the agro-industrial complex are presented. Key directions and initiatives will allow, with the help of data, to carry out the digital transformation of the agro-industrial complex using digital platforms. The digital platform will allow each participant to receive reliable, timely information about the promotion of goods along the entire chain from manufacturer to consumer. The analysis shows that the introduction of digitalization will allow, on average, to increase the volume of consumption of agricultural products in the republic.
Keywords: Digitalization; agro-industrial complex; agriculture